How Intensive Is Competition in the Emerging Markets? : An Analysis of Corporate Rates of Return from Nine Emerging Markets - Singh, Ajit (IMF Working Papers; Working Paper, 1999)
This large empirical study of corporate profitability in emerging markets during the 1980s and 1990s measures the intensity of competition. Data on corporate rates of return, profit margins, and output-capital ratios reveal that the recent liberalization has been associated with reduced corporate profit margins and improved capital utilization efficiency. The paper also analyzes persistency in corporate profitability and finds that competitiveness was no less intense in developing countries than in advanced countries. Although the paper is not directly concerned with the Asian crisis, it provides evidence on important structural hypotheses about the crisis.